Humic acid-phenolic resin based microporous hard carbon material as well as preparation method and application thereof
Through cross-linking reaction of humic acid and phenolic resin and high-temperature carbonization treatment, hard carbon materials with large layer spacing and rich micropores were prepared, which solved the problems of small layer spacing and insufficient specific surface area of existing hard carbon materials, and improved the diffusion ability and electrochemical properties of sodium ions.
Patent Information
- Application Number
- CN202411730058.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
AI Technical Summary
The application of existing hard carbon materials in sodium ion batteries and supercapacitors is due to the small layer spacing and insufficient specific surface area, which leads to inconvenient diffusion of sodium ions and limits the performance of the material.
The network structure is formed by cross-linking reaction between humic acid and phenolic resin, and a humic acid-phenolic resin-based microporous hard carbon material with large layer spacing and rich micropores is prepared through high-temperature carbonization treatment.
It improves the storage capacity of hard carbon materials and the rapid transfer capacity of sodium ions, enhancing its electrochemical performance in sodium ion batteries and supercapacitors.
Smart Images

Figure CN119660708A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to hard carbon, in particular to a humic acid-phenolic resin-based microporous hard carbon material and a preparation method and application thereof. Background Art
[0002] Hard carbon is a carbon material with short-range order, long-range disorder and difficulty in graphitization. It has the characteristics of wide raw material sources, low cost, low sodium storage potential (~0.1V) and excellent cycle stability. It is considered to be the most promising negative electrode material for sodium ion batteries.
[0003] Humic acid is a natural, low-cost organic substance in lignite. It has a high carbon content and a low oxidation state. The molecule contains a large number of functional groups such as carboxyl, phenolic hydroxyl, and aldehyde. Under the action of a certain curing agent, it can form a polymer network microporous structure with phenolic resin. The precursor of the carbonized polymer network microporous structure has a certain effect on increasing the hard carbon interlayer spacing and regulating the specific surface area, which is of great significance to reducing the production cost of hard carbon materials and improving the performance of hard carbon materials.
[0004] In recent years, there have been occasional reports on the preparation of hard carbon materials using humic acid or phenolic resin as precursors. However, the prepared hard carbon materials have a small interlayer spacing, which is not conducive to the rapid diffusion of sodium ions, thus limiting their application in sodium ion batteries and supercapacitors. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a humic acid-phenolic resin based microporous hard carbon material and its preparation method and application, to prepare a hard carbon material rich in micropores and with a large interlayer spacing, which is beneficial to improve the storage capacity of the hard carbon material and the rapid transmission of sodium ions.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a humic acid-phenolic resin-based microporous hard carbon material comprises the following steps:
[0008] Step 1, mixing 90-300 mL of a 1-5 mol / L nitric acid solution with 30-100 mL of a 1-5 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0009] Step 2, dissolving 15-50 g of humic acid precursor in mixed solution A, stirring to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, placing the hydrothermal kettle in an oven, heating to 120-200° C., keeping warm for 20-35 hours, cooling to room temperature, centrifugally washing, drying and grinding in sequence to obtain purified humic acid;
[0010] Step 3, dissolving 1-5 g of purified humic acid in 10-30 mL of 28% ammonia water, stirring at 50-100° C. to obtain solution C; weighing 0.1-5 g of phenolic resin and adding it to solution C, stirring continuously at 50-100° C. to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 60-150° C., standing for 8-24 hours to allow intermolecular cross-linking reaction to occur, and then drying and grinding to obtain product E;
[0011] Step 4: Place product E into a tubular furnace, and heat the temperature from room temperature to 500-1200° C. at a heating rate of 2-20° C. / min under a nitrogen atmosphere, and keep the temperature for 1-4 hours to obtain a humic acid-phenolic resin-based microporous hard carbon material.
[0012] Furthermore, the filling ratio of the hydrothermal kettle in step 2 is 35% to 75%.
[0013] Furthermore, the centrifugal washing in step 2 is performed by centrifugal washing with deionized water for 3 to 5 times.
[0014] Furthermore, the drying in step 2 is carried out in a forced air drying oven at 60 to 150° C. for 2 to 8 hours.
[0015] Furthermore, the average particle size of the humic acid purified in step 2 is 3 to 6 μm.
[0016] Furthermore, the stirring in step 3 is carried out using a magnetic stirrer with a stirring rate of 100 to 200 r / min, and the continuous stirring time is 30 to 100 min.
[0017] Furthermore, the drying in step 3 is performed in a blast drying oven at 80-120°C.
[0018] Furthermore, the average particle size of the product E in step 3 is 5 to 15 μm.
[0019] A humic acid-phenolic resin-based microporous hard carbon material, characterized in that the average particle size is 2 to 50 μm and the specific surface area is 5 to 30 m 2 g -1 , the interlayer spacing is 0.35~0.40nm.
[0020] A humic acid-phenolic resin-based microporous hard carbon material is used as a negative electrode material for sodium ion batteries and a negative electrode material for supercapacitors.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] The present invention adopts a two-step method of cross-linking reaction-high temperature carbonization to synthesize a humic acid-phenolic resin-based microporous hard carbon material. Not only are the raw materials easily available and low in cost, but the preparation process does not require large-scale equipment and harsh reaction conditions, and does not require a morphology control agent. The prepared humic acid-phenolic resin-based microporous hard carbon material has a high yield. According to measurements, the residual carbon rate of humic acid is between 60 and 75%, and the residual carbon rate of phenolic resin is about 80%. In addition, the preparation process of the present invention does not require post-treatment, is environmentally friendly, and can be suitable for large-scale production.
[0023] The present invention forms a network structure through the cross-linking reaction of humic acid and phenolic resin, and obtains a humic acid-based microporous hard carbon material with a large interlayer spacing after carbonization, which is beneficial to the rapid diffusion of sodium ions. As a negative electrode material for sodium ion batteries and a negative electrode material for supercapacitors, the electrochemical performance of sodium ion batteries and supercapacitors can be improved. Moreover, by adjusting the dosage of humic acid and phenolic resin, the heating rate and the carbonization temperature, the degree of the cross-linking reaction can be regulated, thereby regulating the interlayer spacing, micropore size and structure of the hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : SEM image of the hard carbon material prepared in Example 1 of the present invention
[0025] Figure 2 : TEM image of the hard carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0027] Example 1
[0028] Step 1, mixing 90 mL of 3 mol / L nitric acid solution with 90 mL of 3 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0029] Step 2, dissolving 15g of humic acid precursor in mixed solution A, stirring for 30min to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, the filling ratio of the hydrothermal kettle is 40%, placing the hydrothermal kettle in an oven, heating to 120°C, keeping warm for 24h, cooling to room temperature, centrifugally washing with deionized water 3 times, collecting the solid product and placing it in a forced air drying oven, drying at 105°C for 6h, cooling, grinding for 2h, and obtaining purified humic acid with an average particle size of 3 to 6μm;
[0030] Step 3, dissolving 5g of purified humic acid in 25mL of 28% ammonia water, stirring at 75°C with a magnetic stirrer at a stirring rate of 100r / min to obtain solution C; weighing 2g of industrial phenolic resin and slowly adding it to solution C, stirring continuously for 60min at 75°C to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 120°C, standing for 24h to allow intermolecular cross-linking reaction to occur, and then drying and grinding for 1h to obtain a product E with an average particle size of 5 to 15μm;
[0031] Step 4: First, place product E into a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 1000° C. at a heating rate of 10° C. / min, and keep it warm for 2 h to obtain a humic acid-phenolic resin-based microporous hard carbon material.
[0032] like Figure 1 As shown, the average particle size of the humic acid-phenolic resin-based microporous hard carbon material prepared in Example 1 is 2 to 50 μm, and the surface pore structure is very rich.
[0033] like Figure 2 As shown, the humic acid-phenolic resin-based microporous hard carbon material prepared in Example 1 has a disordered carbon layer structure with an average interlayer spacing of 0.37 nm, which is conducive to the rapid transmission of sodium ions.
[0034] Example 2
[0035] Step 1, mixing 200 mL of 2 mol / L nitric acid solution with 100 mL of 2 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0036] Step 2, dissolving 30g of humic acid precursor in mixed solution A, stirring for 40min to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, the filling ratio of the hydrothermal kettle is 65%, placing the hydrothermal kettle in an oven, heating to 150°C, keeping warm for 28h, cooling to room temperature, centrifugally washing with deionized water 4 times, collecting the solid product and placing it in a forced air drying oven, drying at 120°C for 8h, cooling, grinding for 2h, and obtaining purified humic acid with an average particle size of 3 to 6μm;
[0037] Step 3, dissolving 4g of purified humic acid in 20mL of 28% ammonia water, stirring at 75°C with a magnetic stirrer at a stirring rate of 150r / min to obtain solution C; weighing 3g of industrial phenolic resin and slowly adding it to solution C, stirring continuously for 70min at 80°C to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 150°C, standing for 16h to allow intermolecular cross-linking reaction to occur, and then drying and grinding for 1h to obtain a product E with an average particle size of 5 to 15μm;
[0038] Step 4: First, put the product E into a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 900° C. at a heating rate of 5° C. / min, and keep it warm for 2 h to obtain a humic acid-phenolic resin-based microporous hard carbon material.
[0039] Example 3
[0040] Step 1, mixing 120 mL of 4 mol / L nitric acid solution with 30 mL of 1 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0041] Step 2, dissolving 20g of humic acid precursor in mixed solution A, stirring for 20min to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, the filling ratio of the hydrothermal kettle is 35%, placing the hydrothermal kettle in an oven, heating to 120°C, keeping warm for 20h, cooling to room temperature, centrifugally washing with deionized water 4 times, collecting the solid product and placing it in a forced air drying oven, drying at 150°C for 2h, cooling, grinding for 1h, and obtaining purified humic acid with an average particle size of 3 to 6μm;
[0042] Step 3, dissolving 2g of purified humic acid in 15mL of 28% ammonia water, stirring at 50°C with a magnetic stirrer at a stirring rate of 100r / min to obtain solution C; weighing 5g of industrial phenolic resin and slowly adding it to solution C, stirring continuously for 30min at 50°C to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 150°C, standing for 8h to allow intermolecular cross-linking reaction to occur, and then drying and grinding for 2h to obtain a product E with an average particle size of 5 to 15μm;
[0043] Step 4: First, put the product E into a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 1200° C. at a heating rate of 15° C. / min, and keep it warm for 1 hour to obtain a humic acid-phenolic resin-based microporous hard carbon material.
[0044] Example 4
[0045] Step 1, mixing 300 mL of 5 mol / L nitric acid solution with 100 mL of 5 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0046] Step 2, dissolving 50g of humic acid precursor in mixed solution A, stirring for 40min to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, the filling ratio of the hydrothermal kettle is 75%, placing the hydrothermal kettle in an oven, heating to 200°C, keeping warm for 30h, cooling to room temperature, washing with deionized water by centrifugation 5 times, collecting the solid product and placing it in a forced air drying oven, drying at 60°C for 8h, cooling, grinding for 3h, and obtaining purified humic acid with an average particle size of 3 to 6μm;
[0047] Step 3, dissolving 1g of purified humic acid in 10mL of 28% ammonia water, stirring at 100°C with a magnetic stirrer at a stirring rate of 200r / min to obtain a solution C; weighing 0.5g of industrial phenolic resin and slowly adding it to solution C, stirring continuously for 50min at 100°C to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 60°C, standing for 20h to allow intermolecular cross-linking reaction to occur, and then drying and grinding for 1.5h to obtain a product E with an average particle size of 5 to 15μm;
[0048] Step 4: First, place product E into a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 500° C. at a heating rate of 2° C. / min, and keep it warm for 4 hours to obtain a humic acid-phenolic resin-based microporous hard carbon material.
[0049] Example 5
[0050] Step 1, mixing 250 mL of 1 mol / L nitric acid solution with 60 mL of 4 mol / L hydrochloric acid solution to obtain a mixed solution A;
[0051] Step 2, dissolving 40g of humic acid precursor in mixed solution A, stirring for 20min to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, the filling ratio of the hydrothermal kettle is 70%, placing the hydrothermal kettle in an oven, heating to 180°C, keeping warm for 5h, cooling to room temperature, centrifugally washing with deionized water 3 times, collecting the solid product and placing it in a forced air drying oven, drying at 80°C for 4h, cooling, grinding for 4h, and obtaining purified humic acid with an average particle size of 3 to 6μm;
[0052] Step 3, dissolving 3g of purified humic acid in 30mL of 28% ammonia water, stirring at 90°C with a magnetic stirrer at a stirring rate of 100r / min to obtain a solution C; weighing 5g of industrial phenolic resin and slowly adding it to solution C, stirring continuously for 100min at 90°C to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 90°C, standing for 12h to allow intermolecular cross-linking reaction to occur, and then drying and grinding for 2h to obtain a product E with an average particle size of 5 to 15μm;
[0053] Step 4: First, place product E into a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 1100° C. at a heating rate of 20° C. / min, and keep it warm for 3 hours to obtain a humic acid-phenolic resin-based microporous hard carbon material.
Claims
1. A method for preparing a humic acid-phenolic resin-based microporous hard carbon material, characterized in that: The steps include: Step 1, mixing 90-300 mL of a 1-5 mol / L nitric acid solution with 30-100 mL of a 1-5 mol / L hydrochloric acid solution to obtain a mixed solution A; Step 2, dissolving 15-50 g of humic acid precursor in mixed solution A, stirring to obtain a mixed suspension B, transferring the mixed suspension B to a hydrothermal kettle, placing the hydrothermal kettle in an oven, heating to 120-200° C., keeping warm for 20-35 hours, cooling to room temperature, centrifugally washing, drying and grinding in sequence to obtain purified humic acid; Step 3, dissolving 1-5 g of purified humic acid in 10-30 mL of 28% ammonia water, stirring at 50-100° C. to obtain solution C; weighing 0.1-5 g of phenolic resin and adding it to solution C, stirring continuously at 50-100° C. to obtain a mixed suspension D, placing the mixed suspension D in a drying oven at 60-150° C., standing for 8-24 hours to allow intermolecular cross-linking reaction to occur, and then drying and grinding to obtain product E; Step 4: Place product E into a tubular furnace, and heat the temperature from room temperature to 500-1200° C. at a heating rate of 2-20° C. / min under a nitrogen atmosphere, and keep the temperature for 1-4 hours to obtain a humic acid-phenolic resin-based microporous hard carbon material.
2. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The filling ratio of the hydrothermal kettle in step 2 is 35% to 75%.
3. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The centrifugal washing in step 2 is performed by centrifugal washing with deionized water for 3 to 5 times.
4. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The drying in step 2 is performed in a forced air drying oven at 60 to 150° C. for 2 to 8 hours.
5. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The average particle size of the humic acid purified in step 2 is 3 to 6 μm.
6. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The stirring in step 3 is carried out by using a magnetic stirrer with a stirring rate of 100 to 200 r / min, and the continuous stirring time is 30 to 100 min.
7. The method for preparing the humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The drying in step 3 is performed in an air drying oven at 80-120°C.
8. The method for preparing a humic acid-phenolic resin-based microporous hard carbon material according to claim 1, characterized in that: The average particle size of the product E in step 3 is 5 to 15 μm.
9. A humic acid-phenolic resin-based microporous hard carbon material prepared by the method according to any one of claims 1 to 8, characterized in that: The average particle size is 2-50 μm, and the specific surface area is 5-30 m 2 g -1 , the interlayer spacing is 0.35~0.40nm.
10. Use of the humic acid-phenolic resin-based microporous hard carbon material according to claim 9 as a negative electrode material for sodium ion batteries and a negative electrode material for supercapacitors.